Implementing a game on mobile phone with telegram APIs - Koh, Elvan Jia Wei (Nanyang Technological University, 2021)
A software program has been developed with Node.js and Telegram APIs. The software program implements the game Mastermind as a Telegram bot. The game is a fun and contactless way for users to play Mastermind while still facilitating conversations among the players. The developed Telegram bot allows single player and multiplayer to play the Mastermind using text-based commands. In the single player mode, the Telegram bot generates a game, acts as the host, gives hints and checks if the game is finished. In the multiplayer mode, the bot generates a game and acts quietly while the players are playing. The players can chat with each other as usual in Telegram while playing the game. The Telegram bot is hosted on the Heroku platform. This report details the development of the software program, including the discussions of the different choices of games, different cloud hosting services, the structure and coding of the program. The various limitations and problems encountered during implementation of the project are also addressed.